The Influence of Teacher’s Infrastructure and Teacher’s Creativity on Teacher’s Performance - Sarmidi, Sarmidi; Ahyani, Nur; Fitria, Happy (Journal of Social Work and Science Education, 2024)
Education is an important aspect of society that requires various skills, strategies, and learning models. Innovation is very important to overcome educational problems. The quality of the learning process depends on organizing and managing input from teachers, students, money, and resources. Creativity in learning is a system that is not easy to control but is very important for effective learning. However, monotonous learning can lead to monotony, lack of motivation, and lack of passion in students. The author observes the poor quality of junior high school teachers in Namang District, the absence of a social studies laboratory, learning media facilities, and certification. Many teachers are not linear in their areas of competence. This research aims to determine the influence of infrastructure and teacher creativity on teacher performance in junior high schools in Namang District, Central Bangka Regency. This research will be conducted at junior high schools in Namang District, Central Bangka Regency, using quantitative research with a descriptive approach. The population is teachers in Namang District with a sample of 53 respondents. The research will be carried out through pre-research, followed by a trial phase, where questionnaires will be distributed. Observational data collection techniques, and documentation. Research suggests improving facilities and infrastructure in schools, especially in UKS rooms, to ensure students can relax and unwind. Teacher creativity is essential for effective teaching, offering a variety of methods and practices to avoid monotony. Apart from that, teacher performance also needs to be improved, especially in providing individual guidance to students who have problems. Schools should encourage active and enthusiastic teachers to increase their overall efforts in education.